Assessing the gap between policy and practice: community health workers’ contributions to nutrition services in Sub-Saharan Africa - Akriti Singh; Mahamadou Mansour Ndiath; Djeinam Toure; Romance Dissieka; Lennie Kyomuhangi Bazira; Carolyne Wanyonyi; Rolf DW Klemm (BMC Health Services Research)
Abstract Background Community health workers (CHWs) are the backbone of healthcare service provision in Africa, particularly in delivering critical health and nutrition services. Despite their pivotal role, there is limited understanding of the alignment between CHW responsibilities as defined in national policies and the actual nutrition services they provide. This study aimed to compare the nutrition-related responsibilities assigned to CHWs in national policies with the nutrition services CHWs report delivering to women and children in six Sub-Saharan African countries: Guinea, Mali, Niger, Côte d’Ivoire, Democratic Republic of Congo (DRC), and Kenya. Methods We combined structured interviews with 735 CHWs from six countries with a document review of national CHW policies and training manuals to assess the alignment between policy and practice in nutrition service delivery. Results The policy documents revealed notable differences in the CHW scope of responsibilities across the six countries. Training for CHWs was inconsistently documented across countries. Financial compensation for CHWs was mentioned in policy documents from five out of six countries, though the nature and amount of compensation varied significantly. Among the CHWs surveyed, a high percentage (68-84%) reported receiving financial compensation. Most CHWs provided promotional services but were more likely to dispense preventive and curative commodities for children (e.g., Vitamin A, deworming, oral rehydration solution, and Zinc) than women (iron-folic acid, intermittent preventive treatment for Malaria). Service provision was closely linked to the training received. Discrepancies were noted between policy-defined responsibilities and reported service delivery, particularly in growth monitoring and promotion and management of wasting. Conclusions This study found a critical need for stronger alignment between policy directives and CHW training and service provision. By informing policy reforms, standardizing training, and guiding resource allocation, our findings can strengthen CHW programs and improve delivery of lifesaving nutrition interventions to women and children—particularly in remote and underserved communities.